Changes in Atmospheric Butanes and Pentanes and Their Isomeric Ratios in the Continental United States. Issue 7 (12th April 2018) - Rossabi, Sam; Helmig, Detlev
Abstract: Nonmethane hydrocarbons have been used as tracers in research on emissions and atmospheric oxidation chemistry. This research investigates source region mixing ratio trends of the nonmethane hydrocarbons i ‐butane, n ‐butane, i ‐pentane, and n ‐pentane, and the ( i / n ) isomeric ratios of these compounds between 2001 and 2015. Data collected at Photochemical Assessment Monitoring Stations, mandated by the U.S. Environmental Protection Agency in ozone nonattainment areas, and data collected at Global Greenhouse Gas Reference Network sites within the National Oceanic and Atmospheric Administration network, and analyzed at the Institute of Arctic and Alpine Research at the University of Colorado‐Boulder, were examined. Among all considered species, linear regression analyses on concentration time series had negative slopes at 81% of sites, indicating predominantly declining butane and pentane atmospheric concentrations. Mostly negative slopes (78% of sites) were found for the ( i / n ) butane and pentane isomeric ratios, including all six and seven statistically significant ( i / n ) butane and pentane trends, respectively. Over the ~15 year investigation period and averaged over all sites, total relative changes were ~30 and 45% for the ( i / n ) ratios of butanes and pentanes, respectively, with a relative increase in the prominence of the n ‐isomers. Most likely causes include changing isomeric ratios in gasoline sector emissions, and increasing influence of oil and natural gas industry emissions. Changes in concentrations and isomeric ratios depend on proximity of contributing emission sources to measurement sites. Key Points: Average atmospheric mixing ratios of the i ‐butane and n ‐butane and i ‐pentane and n ‐pentane isomers have been decreasing at most of the urban sites considered Over 15 years, the isomeric ratio of the two alkane pairs has dropped by an average of 30–45%, with a relative increase of the n ‐isomers Deriving national trends for mixing ratios and emission inventories from these data is impeded by the variability in results between sites